Molecular screening reveals non-uniform malaria transmission in western Kenya and absence of Rickettsia africae and selected arboviruses in hospital patients - Chiuya, T.; Villinger, J.; Falzon, Laura C.; Alumasa, Lorren; Amanya, Fredrick; Bastos, A.D.S.; Fèvre, Eric M.; Masiga, D.K. (Springer, 2022)
Background In sub-Saharan Africa, malaria is the common diagnosis for febrile illness and related clinical features, resulting in the under-diagnosis of other aetiologies, such as arboviruses and Rickettsia. While these may not be significant causes of mortality in malaria-endemic areas, they affect the daily life and performance of affected individuals. It is, therefore, important to have a clear picture of these other aetiologies to institute correct diagnoses at hospitals and improve patient outcomes.